Disaster Preparedness and Associated Factors Among Emergency Nurses in Guangdong Province, China: A Descriptive Cross-Sectional Study. (1st December 2023) - Wang, Jia; Sun, Xinglan; Lu, Sihui; Wang, Fen; Wan, Meijuan; Chen, Hanxi; Tan, Yibing
ABSTRACT: Objective: The purpose of this study was to examine the prevalence of disaster preparedness and to explore associated factors among emergency nurses in Guangdong Province, China. Methods: In this descriptive, cross-sectional study, the mainland China version of the Disaster Preparedness Evaluation Tool was used to collect data from 633 nurses working in 26 emergency departments, in August 2018. Descriptive analyses were used to examine the disaster preparedness, and multiple linear regression analysis was used to investigate associated factors. Results: The perceived disaster preparedness of emergency nurses was at a moderate level. Among the 5 dimensions, the score for disaster management was lowest. Emergency nurses' disaster training (r = .26; P < 0.001) and drill experiences (r = .22; P < 0.001) were significantly correlated with disaster preparedness. Six significant factors associated with disaster preparedness were identified in this study: age, gender, disaster training experience, disaster drill experience, willingness, and educational level ( R 2 = .14; F = 18.20; P < 0.001). Conclusions: Hospitals and nurse managers should carry out interdisciplinary and multidisciplinary cooperation to improve emergency nurses' disaster preparedness, especially disaster management. Organizing disaster simulation exercises, providing psychological support and safety considerations, and formulating disaster nursing training programs may be beneficial for emergency nurses' disaster preparedness.